SMU 95 LIBRARY SYSTEM DATABASE APPLICATIONS USING VISUAL BASIC 6.0 - Saiful Anas; Sahni D.P. SKom.MM Sahni D.P. SKom.MM (Jurnal Sistem Informasi, 2001)
The school library is one type of library in general,. So it be said that the schoollibrary also be an understanding of the translation from an understanding of thelibrary in general. The school library manifested by the existence of a particular unitin an institution called school. School libraries, like public libraries, as well as acollection of library materials consisting of books, slides, magazines, newspapers andothers. All library materials are arranged in a certain room within the scope of theschool, arranged systematically,so that users can use the library facilities asefficiently and as much as possible.The purpose of this writer in scientific writing is to change the listing of rental andreturn of the manual is a computerized system, using microsoft visual basicapplication database.